Thermal exchange, physiological variables and thermography in creole horse under heat stress - Neila Lidiany Ribeiro; Dermeval Araújo Furtado; Wallace Barbosa do Nascimento; Nubia Michelle Vieira da Silva; Airton Gonçalves de Oliveira; Maria Luiza Coelho Cavalcante; Brendo Junior Pereira Farias; Tiago Lira Souza Santos; Ricardo de Sousa Silva; Geovergue Rodrigues de Medeiros (Smart Agricultural Technology)
The aim of the study was to evaluate physiological variables invasively and non-invasively and heat exchange in Nordestina breed horses, and to determine which variables have the greatest discriminating power in terms of adaptive profile, using canonical and stepwise discriminant analysis. Seven adult horses were used, 3 females and 4 stallion males, which were housed from birth in the property's paddocks with ad libitum access to native pasture, concentrate in the trough and water, remaining in these conditions during the experimental period. The thermal comfort index (TCI) values ​​above 65 are considered severe heat stress for horses. The rectal temperature, respiratory rate and heart rate of the females were similar (P > 0.05) between the periods and these variables remained within the limit for the equine species, even with the rise in air temperature in the afternoon and the high TCI, demonstrating the animals' adaptive capacity. The Nordestina breed showed physiological values within the standard for the species, even with the ambient temperature above the thermal comfort zone in both periods (30.09 and 35.05 °C), being efficient at dissipating heat through the skin and respiratory system, keeping the rectal temperature within the standard for the species